A modular cell controller architecture for a flexible manufacturing system - Carvalho, José Augusto (2010)
The need to optimize manufacturing systems operation has originated continuous effort in the developmeut of control system architectures. These have been freed from original rigid centralized structures evolving in such a way that attribute more autonomy to each control subsystem. The subsystems have then become specialized in the different tasks needed to control each manufacturing process. In the present work, an architecture for a cdl controller, composed of modules with a significant degree of autonomy, is presented.